(untitled) (Academia Science Repository, 2023)
This review was conducted to explain the efficacy of some herbals as a growth and performance promoter in broiler. The importance and use of herbal remedies has been reviewed systematically. Garlic can be utilized to successfully increase broiler growth, Aloe vera has been shown to be beneficial in the treatment of wounds and the treatment of diabetes. Fenugreek has the ability to provide ruminant animals with high-quality feed. Nettle leaves were found to boost body weight increase and feed conversion efficiency for broilers. The effects of Thyme extracts or essential oils on a range of meat varieties, including pig, beef, and lamb, have been thoroughly examined and reported after their direct addition. The weight gain of Cobb broilers is dramatically increased by 16.97% when O. sanctum aqueous extracts is added to water compared to the controls.